Biological activity of the venom from Anthothoe chilensis (Lesson, 1830)(Actiniaria: Sagartiidae) - Retuerto, Fernando (2007)
This paper reports on biochemical characteristics, hemolytic activity, cytolytic and citotóxic of three fractions venom from the sea anemone Anthothoe chilensis. The arms of 78 individuals of A. chilensis, from the Isle Cabinza-San Lorenzo, Lima, were treated to obtain a filtrate (Ft), which is divided by precipitation with three points of saturation with cold acetone: I (20%), II (50%), III (80%). The Ft showed 1,8 mg/mL of protein concentration. Test of total carbohydrate detection showed the presence of 1,401 mg of glucose/ml of solution in Ft. SDS-PAGE showed proteins between 14 to 94 kDa, almost were glycoproteins. Hemolytic activity was assayed on human erythrocytes showing positive result the fractions II and I. The fraction III was highest phospholipasic activity. Evaluating the proteolytic activity on casein was observed that the fraction I has the highest activity. Cytotoxic and cytological effects were evaluated in sea urchin embryos Tetrapigus niger. The morphologic abnormalities were evaluated at 48 hours of developing. Cytological abnormalities were observed at late gastrule stage. All acetonic fractions caused abnormalities in embryonic development. Delay of development, morphologic abnormalities like lysis at the blastula and exogastrulation, cytological abnormalities like heteropycnosis, giant nuclei and cellular spaces were observed. The fraction II was more cytotoxic, producing a 75,52 ± 5,5% mortality on early stages with 1,0 μg/mL. The fraction I had the highest anomalies quantity on survivor embryos, 64,15 ± 4,2% with 1,3 μg /mL. The fraction III was less toxic.